2012
DOI: 10.1111/j.1742-481x.2012.01042.x
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating gold into nanocrystalline silver dressings reduces grain boundary size and maintains suitable antimicrobial properties

Abstract: Nanocrystalline silver dressings are widely known to be potent antimicrobial and anti-inflammatory agents and have long been used to treat topical wounds. Gold is known to be a strong anti-inflammatory agent and has been used in the treatment of rheumatoid arthritis for >70 years. The purpose of this work was to study the effect of incorporating gold into nanocrystalline silver dressings from antimicrobial and anti-inflammatory perspectives. Gold and silver dressing alloys were created by direct current magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 26 publications
3
11
1
Order By: Relevance
“…Foundational work by Kevin Unrau on nanocrystalline silver‐gold dressings can serve as a comparison here. Unrau found that there was a trend of less ammonia soluble silver release with increasing gold content, which was not proportional to the amount of gold increase in the alloy 4 . This was also seen in the results here, where Ag65 had >65% of the ammonia soluble silver as Ag100, and Ag35 had <35%.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Foundational work by Kevin Unrau on nanocrystalline silver‐gold dressings can serve as a comparison here. Unrau found that there was a trend of less ammonia soluble silver release with increasing gold content, which was not proportional to the amount of gold increase in the alloy 4 . This was also seen in the results here, where Ag65 had >65% of the ammonia soluble silver as Ag100, and Ag35 had <35%.…”
Section: Discussionsupporting
confidence: 77%
“…The log reductions for all samples had similar results, which was not expected. This differs from previous work, where it was found that total kills only occurred in S. aureus and P. aeruginosa for the higher silver content (Ag100 and Ag80) 4 . However, the nitric acid digest for total silver was not performed for this study.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…The inherent beneficial effects of AuNPs have awaken notable interest in the treatment of topical wounds and skin pathologies such as rheumatoid arthritis, but potential cytotoxic responses of AuNPs should be considered when these products come into direct contact with skin, as it is the largest organ of the body and an important route of entry for NPs into the human organism. [22,29,38] Furthermore, since particle size is considered as a crucial factor when describing AuNP-induced cytotoxicity, in this study we evaluated the cytotoxic effects produced by three different AuNPs in size on NHDF cells and the role of oxidative stress in the observed cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%